Cirsium wulongense (Asteraceae, Cardueae), a new species from Chongqing, China - Jin, Zi-Chao; Chen, Feng; Chen, You-Sheng (Phytotaxa, 2024)
Cirsium wulongense (Asteraceae), a new species from Xiannü Shan in Wulong district, Chongqing, China, is described and illustrated. This new species is similar to C. sichuanense in its nodding capitula and white corolla, but differs by having leaves discolorous (vs. concolorous), abaxially grayish white and densely tomentose (vs. green, glabrous or sparsely pubescent with long multicellular hairs) and phyllaries subulate (vs. acute) at apex. It is also closely similar to C. fanjingshanense in the campanulate involucre and patent to reflexed phyllaries, but differs by its stems pubescent with densely long multicellular hairs (vs. subglabrous), leaves pinnatilobate to pinnatipartite (vs. undivided), discolorous (vs. concolorous), abaxially grayish white and densely tomentose (vs. green and glabrous), and corolla white (vs. purplish).